MATHEMATICAL MODEL OF CORROSION INSIDE METAL WATER PIPES - Nguyen, Huy; Nguyen, Ngoc (SWorldJournal, 2020)
In water supply systems, one of the most important factors is corrosion of pipelines from steel and cast-iron pipes, an increase in pressure losses, which reduces water flow and increases energy consumption. Excessive corrosion intensity is determined by